2008
DOI: 10.1063/1.2973154
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of leakage current in the dielectric layer due to Cu migration during bias temperature stress

Abstract: The dielectric breakdown by Cu ion migration under applied bias is important for the reliability of damascene Cu interconnects as well as Cu through-hole bias in three-dimensional interconnects. The mechanism responsible for the leakage current through the dielectric during bias temperature stress is investigated in Cu/SiO2 and Al/SiO2 metal-insulator-semiconductor samples. When a constant electric field is applied, a gradual increase in leakage currents was observed in the case of Cu/SiO2, but no increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…SiO 2 , HfO 2 , Al 2 O 3 ). [2][3][4][5][6] In these oxides the percolation model is the most accepted theory for BD formation, and it states that the insulating capability is lost due to the formation of a defective conductive nanofilament (CNF) connecting the two sides of the dielectric. 7 When the last defect that forms the filament is trapped the local currents increase sharply several orders of magnitude, leading to the accumulation of thermal heat at the BD site.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…SiO 2 , HfO 2 , Al 2 O 3 ). [2][3][4][5][6] In these oxides the percolation model is the most accepted theory for BD formation, and it states that the insulating capability is lost due to the formation of a defective conductive nanofilament (CNF) connecting the two sides of the dielectric. 7 When the last defect that forms the filament is trapped the local currents increase sharply several orders of magnitude, leading to the accumulation of thermal heat at the BD site.…”
Section: Introductionmentioning
confidence: 99%
“…7 When the last defect that forms the filament is trapped the local currents increase sharply several orders of magnitude, leading to the accumulation of thermal heat at the BD site. 2 This supplies nearby atoms (in both the oxide and adjacent metallic electrodes) with a high energy that produces avalanche currents, 3 lateral BD spot propagation, 4 and electro-migration, 5 which ultimately results in irreversible surface extrusion (hillock formation) 6,[8][9][10] and the dramatic failure of the entire device. Avoiding BD-induced irreversible damage in dielectrics is highly desirable to enhance the reliability and lifetime of digital electronic devices, 11 but until now all dielectrics known (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dielectric constant (k) can be extracted by fitting to SC and PF. The dominant mechanism of leakage can be revealed by comparing dielectric constant from literature and that from fitting [4,5]. …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is important to understand TDDB failures for AC condition. Hwang et al studied the effect of forward and reverse bias during TDDB using a metal-insulator-semiconductor (MIS) structure [4]. They demonstrated that the migrated Cu ions move back during reverse bias and hence leakage current is recovered by removing the extrinsic defects.…”
Section: Introductionmentioning
confidence: 98%